A bioavailable baseline strontium isotope map of southwestern Turkey for mobility studies. (June 2021) - Wong, Megan; Grimes, Vaughan; Steskal, Martin; Song, Justin; Ng, John; Jaouen, Klervia; Lam, Vienna Chichi; Richards, Michael
Highlights: We present an Sr map of SW Turkey based on analysis of modern plants and snails. This map is essential to archaeological research using Sr to assess provenance. The bioavailable Sr broadly follows the underlying geology. The western coastal area has higher Sr ratios than the more eastern inland areas. Abstract: We present here a map of bioavailable strontium for Southwestern Turkey derived from measurements of modern plants and mollusk (land snail) shells from various geological areas. Samples were collected from 87 locations and strontium isotope measurements were made on 283 plant and mollusk samples. The plants consisted of deep-rooted, medium-rooted and shallow-rooted species each sampling strontium from different water sources. The data was interpolated to produce a predictive strontium isotope map ('Sr-isoscape') of the region. Despite the complex underlying geology of this region the bioavailable Sr values broadly grouped into two separate areas, related to the age of the underlying bedrock. These results provide a baseline for interpretation of strontium isotope values of archaeological samples to help understand past animal and human mobility, and can also be used by researchers in a range of other disciplines that incorporate strontium analysis for mobility, including animal ecology and forensics.